2015
DOI: 10.1007/s12029-015-9782-4
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated Expression of E-cadherin and TP53 in Patients with Gastric Diseases: the Involvement of H. pylori Infection and Its Virulence Markers

Abstract: No evidence was found of the involvement of the cagA and vacA genes in the decreased expression of E-cadherin and TP53. The process of carcinogenesis is complex, and the decrease of the E-cadherin gene expression and TP53 gene expression appears to contribute significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…These results support previous studies 21, 28-31 , which demonstrate the up-regulation of many of these miRNAs in GC. These miRNAs regulate 18 driver genes (tumor suppressor genes; Table S4A), including APC 60 , RUNX1 61 , EP300 62-63 , KLF4 64-65 , PTEN 66-67 , TP53 68 , RB1 69 , SMAD2 70-71 and SMAD4 72-73 , which have already been reported to be down-regulated in GC. Studies has shown that hsa-miR-10a , -miR-21 , -miR-135b , -miR-148a , -miR-150 , -miR-215 and -miR-483 regulate important processes for the establishment and progression of gastric tumors, such as cell cycle progression, migration, proliferation, invasion, apoptosis and metastasis 56, 61, 74-81 .…”
Section: Discussionmentioning
confidence: 99%
“…These results support previous studies 21, 28-31 , which demonstrate the up-regulation of many of these miRNAs in GC. These miRNAs regulate 18 driver genes (tumor suppressor genes; Table S4A), including APC 60 , RUNX1 61 , EP300 62-63 , KLF4 64-65 , PTEN 66-67 , TP53 68 , RB1 69 , SMAD2 70-71 and SMAD4 72-73 , which have already been reported to be down-regulated in GC. Studies has shown that hsa-miR-10a , -miR-21 , -miR-135b , -miR-148a , -miR-150 , -miR-215 and -miR-483 regulate important processes for the establishment and progression of gastric tumors, such as cell cycle progression, migration, proliferation, invasion, apoptosis and metastasis 56, 61, 74-81 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous evaluations obtained by qPCR method on intestinal GCs gave variable results with reports ranging from a clear decrease [11, 21] to a non-significant difference [22, 23] in CDH1 expression in cancer compared to the normal counterpart. Therefore, through the implementation of the more precise dPCR in our quantification, we were able to provide evidence on the downregulation of CDH1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that Helicobacter pylori ( H. pylori ), which is a primary risk factor for IGC, partially mediates the transformation of the normal gastric mucosa by targeting CDH1 transcription and protein expression levels [8, 11, 12]. Small regulatory RNAs (micro-RNAs) have also been associated with a decrease of E-cadherin expression in IGC; in particular, the loss of miR-101 results in the up-regulation of EZH2, an inhibitor of E-cadherin, thus reducing its expression and promoting tumor progression [13].…”
Section: Introductionmentioning
confidence: 99%
“…From a molecular genetic perspective, both H. pylori infection [ 29 ] and LPR [ 30 ] are associated with a decreased expression of E-cadherin . This can then reduce the apoptosis of HEp-2 cells, which are considered to originate from human laryngeal carcinoma [ 31 ].…”
Section: Introductionmentioning
confidence: 99%